Divórcio extrajudicial obrigatório e seus efeitos - Konrad, Mário Alberto (2010)
The argument put forward is the only non-judicial divorce, procedure, therefore, required when one or both spouses wish to end the marriage. Excluding the Judiciary of the extinction of marriage, although it may be asked the judiciary to define the effects of reflections, as a guard and feed the children, maintenance between spouses, use the name and division of property. The existence of children unable extrajudicial not prevent the dissolution of marriage, though in that case, be subject to approval by the Public Prosecutor of the agreement regarding the custody of parents and food to children, any court decision, if not preserved their interests. In this respect, helped the Portuguese civil law. Natural consequence is the separation between the end of the bond and its effects. Except as regards the interests of the children unable unavailable, all other details are available on the likes of rights, whereby the divorciandos deliberate on them freely, without government intervention. Failing agreement, however, the ruling may be sought even after the termination of the bond. Plays an important role in assisting in setting these mediation effects, optional tool for use by spouses. The thesis also bolsters the amended wording of § 6 of art. 226 of the Federal Constitution under the First Amendment 66. The change eliminated the separation and the discussion of the blame for ending the marriage, and removed the time limits for obtaining divorce. Facilitated, therefore, the extinction of the marriage bond. On that path, plus the experience of consensual divorce out of court, introduced by Law 11.441/2007, is the proposal for mandatory extra-judicial divorce, as facilitator of the extinction of marriage, merely by exercising the right of the spouse of potestative no longer want to stay married and against which no defense possible, ie there dispute. The rapid dissolution of the marital bond via registry, and relieve the Judiciary, it is shown in accordance with the constitutional principles of human dignity and freedom, among others, and releases the spouses to form a new family of marriage